KB-68A7.1 Inhibits Hepatocellular Carcinoma Development Through Binding to NSD1 and Suppressing Wnt/β-Catenin Signalling - Zhang, Shuhua; Xu, Jianqun; Cao, Huan; Jiang, Mi; Xiong, Jun (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is one of the most lethal malignancies with extremely poor prognosis. Therefore, uncovering the critical molecules involved in HCC progression and prognosis are urgently needed. In this study, through combining public dataset and our cohort, we found a novel prognosis-related long noncoding RNA KB-68A7.1 in HCC. KB-68A7.1 was lowly expressed in HCC, and its low expression was associated with large tumor size, aggressive clinical characteristics, and poor overall survival. Gain- and loss-of-function assays demonstrated that KB-68A7.1 restricted HCC cellular proliferation, induced HCC cellular apoptosis, and suppressed HCC cellular migration and invasion in vitro. Xenograft assays demonstrated that KB-68A7.1 restricted HCC tumor growth and metastasis in vivo. These functional assays suggested KB-68A7.1 as a tumor suppressor in HCC. Histone methyltransferase nuclear receptor binding SET domain-containing protein 1 (NSD1) was found to bind KB-68A7.1. KB-68A7.1 is mainly localized in cytoplasm. The binding of KB-68A7.1 to NSD1 sequestrated NSD1 in cytoplasm, leading the reduction of nuclear NSD1 level. Through decreasing nuclear NSD1 level, KB-68A7.1 reduced di-methylation of histone H3 at lysine 36 (H3K36me2) and increased tri-methylation of histone H3 at lysine 27 (H3K27me3) at the promoter of WNT10B, a target of NSD1. Thus, KB-68A7.1 repressed WNT10B expression. The expression of WNT10B was negatively correlated with KB-68A7.1 in HCC tissues. Through repressing WNT10B, KB-68A7.1 further repressed Wnt/β-catenin signaling. Functional rescue assays showed that overexpression of WNT10B reversed the tumor suppressive roles of KB-68A7.1, and while the oncogenic roles of KB-68A7.1 depletion were also abolished by Wnt/β-catenin signaling inhibitor. Overall, this study identified KB-68A7.1 as a lowly expressed and prognosis-related lncRNA in HCC, which inhibited HCC progression through binding NSD1 and suppressing Wnt/β-catenin signaling.